Yin Huo Tang, a traditional Chinese herbal formula, relives ovariectomy and empty bottle stimulation-induced menopause-like symptoms in mice - Ye, Yang; Zhang, Bo; Li, Yan; Xu, Hong-Dan; Liu, Xiu-Min; Huang, Shu-Ming; Wang, Rui; Li, Dong (Frontiers in Endocrinology, 2022)
Background: Yin Huo Tang (YHT), a traditional Chinese herbal formula, is effectively used for the clinical treatment of menopause-like symptoms in China. This study aimed to investigate its efficacy on menopause-like symptoms in mice using behavioral tests and histopathological assessment, and to determine its possible mechanism of action based on network pharmacology. Methods: Liquid chromatography-mass spectrometry (LC-MS) technology was used to identify the potential active ingredients of YHT. In mice, menopause-like symptoms were induced by combination of bilateral ovariectomy and empty bottle stimulation. The mice were then treated with the YHT aqueous extract for three weeks. Behavior, sleep state, body weight, organ index, and histomorphology were analyzed separately. Additionally, network pharmacology and molecular docking were used to predict the mechanisms underlying the action of YHT. Finally, serum estradiol was quantified to preliminarily verify the results of network pharmacology. Results: YHT not only improved the behavior of mice (attack and explore behavior reduced; modify behavior increased) but also ameliorated the sleep state (sleep time increased and incubation time reduced). YHT reduced body weight, increased uterine weight, and improved the histomorphology of some organs. Network pharmacology and molecular docking analyses revealed that the estrogen signaling pathway might play a key role in attenuating menopause-like symptoms. Furthermore, YHT treatment reversed the reduction in serum estradiol levels. Conclusions: YHT alleviates menopause-like symptoms in a mouse model, providing a rationale for using it as a potential therapeutic strategy.